The B2 receptor of bradykinin is not essential for the post-exercise increase in glucose uptake by insulin-stimulated mouse skeletal muscle - Schweitzer, G. G; Castorena, C. M; Hamada, T; Funai, K; E. B. Arias; Cartee, G. D (Physiological research, 2011)
Bradykinin can enhance skeletal muscle glucose uptake (GU), and exercise increases both bradykinin production and muscle insulin sensitivity, but bradykinin's relationship with post-exercise insulin action is uncertain. Our primary aim was to determine if the B2 receptor of bradykinin (B2R) is essential for the post-exercise increase in GU by insulin-stimulated mouse soleus muscles. Wildtype (WT) and B2R knockout (B2RKO) mice were sedentary or performed 60 minutes of treadmill exercise. Isolated soleus muscles were incubated with [(3)H]-2-deoxyglucose +/-insulin (60 or 100 microU/ml). GU tended to be greater for WT vs. B2RKO soleus with 60 microU/ml insulin (P=0.166) and was significantly greater for muscles with 100 microU/ml insulin (P<0.05). Both genotypes had significant exercise-induced reductions (P<0.05) in glycemia and insulinemia, and the decrements for glucose (~14 %) and insulin (~55 %) were similar between genotypes. GU tended to be greater for exercised vs. sedentary soleus with 60 microU/ml insulin (P=0.063) and was significantly greater for muscles with 100 microU/ml insulin (P<0.05). There were no significant interactions between genotype and exercise for blood glucose, plasma insulin or GU. These results indicate that the B2R is not essential for the exercise-induced decrements in blood glucose or plasma insulin or for the post-exercise increase in GU by insulin-stimulated mouse soleus muscle.
Keywords: kondiční příprava zvířat; receptor bradykininu B2; lidé; myši; Mice; krevní glukóza; Animals; Humans; Mice, Knockout; zvířata; kosterní svaly; Genotype; Receptor, Bradykinin B2; myši knockoutované; Muscle, Skeletal; genotyp; Blood Glucose; inzulin lidský; Insulin, Regular, Human; Physical Conditioning, Animal